PRESIDENTIAL SPEECHES AS INSTRUMENTS OF DIPLOMACY: A COGNITIVE-PRAGMATIC PERSPECTIVE ON STRATEGIC COMMUNICATION - Nafosat Abdullayevna Dillayeva (International Journal of Literature and Language Studies, 2026)
In contemporary international relations, presidential speeches have become an essential instrument of diplomacy, extending beyond their traditional role of political communication. Through public addresses, presidents articulate foreign policy objectives, construct national identities, influence international audiences, and contribute to the formation of diplomatic relationships. This article examines the role of presidential speeches in diplomacy through a cognitive-pragmatic framework that integrates Cognitive Linguistics, Speech Act Theory, and Strategic Communication Theory. Particular attention is paid to conceptual metaphors, framing mechanisms, speech acts, and narrative construction as linguistic tools that facilitate diplomatic influence. The study argues that presidential discourse functions not merely as a medium for transmitting information but as a strategic diplomatic practice capable of shaping international perceptions and promoting national interests. By analyzing the interaction between language, cognition, and diplomacy, this research contributes to contemporary studies of political discourse and international communication.